Pengaruh Dimensi Kualitas Pelayanan dan Manajemen Hubungan Pelanggan (Customer Relationship Management) terhadap Kepuasan Pelanggan pada Restoran Penyet Ria Madiun - Puspita, Maya Dita (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
This study aim to explain the effect of service quality dimensions consist is (tangible, reliability, responsiveness, assurance, and empathy) and customer relationship management to customer satisfaction in the Penyet Ria Restaurant Madiun. The research instrument used a questionnaire distributed to 100 customer Penyet Ria Restaurant Madiun taken using purposive sampling. Using multiple linier regression analysis. Result of this study explain that the variable dimensions of service quality and customer relationship management partial tested, only tangible, reliability, responsiveness, and customer relationship management have significant effect to customer satisfaction in the Penyet Ria Restaurant Madiun, but the variable assurance and emphaty no significant effect to customer satisfaction in the Penyet Ria Restaurant Madiun. The dominant factor effect to customer satisfaction in the Penyet Ria Restaurant Madiun is variable reliability.